HUBUNGAN KADAR HEMOGLOBIN IBU HAMIL DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD Dr.MOEWARDI SURAKARTA - Mahmudah, Rofiatun; Sulastri, Sulastri (Universitas Muhammadiyah Surakarta, 2011)
Newborn death associated with obstetric complications and low maternal health status during pregnancy and childbirth. The main cause of neonatal deaths are neonatal asphyxia. The results of preliminary studies obtained that the data during period of January 1st to December 31st, 2010 there were 1736 babies born in which 996 infants who were treated at high risk infants room, 276 infants were treated for asphyxia. The purpose of this study was to determine the relationship between hemoglobin levels of pregnant women with the incidence of neonatorum asphyxia at Dr. Moewardi Hospital Surakarta. This type of research is descriptive correlative with retrospective data collection methods. The number of samples is 100 patients. The sampling technique in this study is simple random sampling, taken from medical records. The instrument used is a checklist that is based on secondary data from the RM 1 (Medical Records 1) on the summary in and out of hospital. Testing research hypotheses using a statistical test spearman rank correlation test. The results showed pregnant women sample who have hemoglobin levels >11 g/dl as many as 96 samples (46%), hemoglobin levels â‰¥11 g/dl as much as 4 samples (4%). As many as 28 infants (28%) who were born with severe heavy asphyxia incidence in the first minute and 72 infants (72%) small asphyxia. There is a relationship between hemoglobin levels on pregnant women with neonatorum asphyxia incidence at Dr. Moewardi Hospital Surakarta, with r = -0.127 and p = 0.034. The conclusion of the research is hemoglobin levels of pregnant with neonatorum asphyxsia have relationship negative which higher the degrees of hemoglobin levels, so more softly the neonatorum asphyxia case